Gaps in the implementation of national core elements for sustainable antimicrobial use in the WHO-African region - Fuller, Walter L.; Aboderin, Aaron O.; Yahaya, Ali; Adeyemo, Adeyemi T.; Gahimbare, Laetitia; Kapona, Otridah; Hamzat, Omotayo T.; Bassoum, Oumar (Frontiers in Antibiotics, 2022)
Background Antimicrobial resistance (AMR) has emerged as a leading global health and economic threat of the 21st century, with Africa bearing the greatest burden of mortality from drug-resistant infections. Optimization of the use of antimicrobials is a core strategic element of the response to AMR, addressing misuse and overuse as primary drivers. Effectively, this requires the whole society comprising not only healthcare professionals but also the public, as well as the government, to engage in a bottom-up and a top-down approach. We determined the progress of African national governments in optimizing antimicrobial drug use. Methods From September 2021 to June 2022, all 47 member states of the World Health Organization African region (WHO AFRO) were invited to participate in a survey determining the implementation of strategies to optimize antimicrobial use (AMU). We used the WHO antimicrobial stewardship (AMS) assessment tool, National core elements—A checklist to guide the country in identifying existing national core elements for the implementation of AMS Programs, to obtain information from national AMR focal persons. The tool consists of four sections—national plans and strategies; regulations and guidelines; awareness, training, and education; and supporting technologies and data—with a total of 33 checklist items, each graded from 0 to 4. The responses were aggregated and analyzed using Microsoft Excel 2020®. Results Thirty-one (66%) of the 47 countries returned completed forms. Only eight (25.8%) countries have developed a national AMS implementation policy incorporating defined goals, targets, and operational plans. There are no budget lines for AMS activities in 23 (74.2%) countries. The WHO Access, Watch, Reserve (AWaRe) classification of optimizing AMU has been integrated into the national essential medicines list or formulary in 19 (61.3%) countries, while the incorporation of the AMS principles and WHO AWaRe classification into national clinical guidelines for the management of infections is present in only 12 (38.7%) and 11 (34.5%) countries, respectively. Although regulations on the prescription-only sale/dispensing of antibiotics are present in 68% of countries, their enforcement is poor. Systems identifying pathogens and antibiotic susceptibility for optimal use of antibiotics are lacking in 38% of countries. Conclusion In Africa, wide gaps exist in the governments’ implementation of the core elements of optimizing antimicrobial drug use. Responding to AMR constitutes a long journey, and technical and financial support needs to be deployed to optimize the use of antimicrobials.